Fatty Acid–Mediated Stromal Reprogramming of Pancreatic Stellate Cells Induces Inflammation and Fibrosis That Fuels Pancreatic Cancer. Issue 10 (November 2017) - Hata, Tomoki; Kawamoto, Koichi; Eguchi, Hidetoshi; Kamada, Yoshihiro; Takamatsu, Shinji; Maekawa, Tomohiro; Nagaoka, Satoshi; Yamada, Daisaku; Iwagami, Yoshifumi; Asaoka, Tadafumi; Noda, Takehiro; Wada, Hiroshi; et al.
Abstract : Objectives: Pancreatic ductal adenocarcinoma is one of the deadliest diseases worldwide. Fatty acids (FAs) have properties that affect both cancer cells and tumor environment. We assessed the effects of FAs on malignant characteristics in a pancreatic cancer and pancreatic stellate cell (PSC) coculture model. This study aimed to clarify the FA signature of PSC-derived inflammation and fibrosis in vitro and in a clinicopathological analysis. Methods: The in vitro model involved coculture of the human pancreatic cancer cell lines PANC-1 and MIA PaCa-2 with human PSCs. Clinical histological samples were analyzed to characterize the surgical margins of samples from patients who received distal pancreatectomies. Results: The pancreatic cancer cells took up lipids from the culture media. Saturated and unsaturated FAs were required to induce inflammatory responses in human PSCs, and the cocultures showed fibrotic changes. Clinical samples from pancreatic ductal adenocarcinoma patients had more fatty and fibrotic changes in the normal tissue in the surgical margins than samples from noncancer patients. Conclusions: Inflammation and fibrosis levels were increased in pancreatic cancer specimens, supporting the in vitro observations and suggesting that PSCs contribute to pancreatic carcinogenesis. Pancreatic stellate cells thus represent a potential therapeutic target for suppressing stromal changes in pancreatic cancer. Abstract : Supplemental digital content is available in the text.